2013
DOI: 10.1038/onc.2013.357
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages mediate gemcitabine resistance of pancreatic adenocarcinoma by upregulating cytidine deaminase

Abstract: Resistance to pharmacologic agents used in chemotherapy is common in most human carcinomas, including pancreatic ductal adenocarcinoma (PDA), which is resistant to almost all drugs, including gemcitabine, a nucleoside analog used as a first-line treatment. Poor survival rates of PDA patients have, therefore, not changed much over 4 decades. Recent data indicated that tumor-associated macrophages (TAMs), which are abundant in the microenvironment of several tumors, including PDA, secrete pro-tumorigenic factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
188
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(194 citation statements)
references
References 48 publications
5
188
0
1
Order By: Relevance
“…The activity of such antitumor molecules could be counteracted by co-administration of THU (40). More recently, decreased chemosensitivity of pancreatic adenocarcinoma to gemcitabine was attributed to macrophage-induced up-regulation of Cyd deaminase (43,44) indicating the high relevance of Cyd deaminase expression in the tumor microenvironment. We confirmed pronounced mycoplasma-associated conversion of dFdC to dFdU when exposing the radiolabeled drug to the spent culture medium (containing free-living mycoplasmas) or tumor cell extracts (containing enzymes of adherent/ intracellular mycoplasmas) of mycoplasma-infected but not uninfected MCF-7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of such antitumor molecules could be counteracted by co-administration of THU (40). More recently, decreased chemosensitivity of pancreatic adenocarcinoma to gemcitabine was attributed to macrophage-induced up-regulation of Cyd deaminase (43,44) indicating the high relevance of Cyd deaminase expression in the tumor microenvironment. We confirmed pronounced mycoplasma-associated conversion of dFdC to dFdU when exposing the radiolabeled drug to the spent culture medium (containing free-living mycoplasmas) or tumor cell extracts (containing enzymes of adherent/ intracellular mycoplasmas) of mycoplasma-infected but not uninfected MCF-7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…M2 and M1 macrophages may concur in favoring PDAC progression and metastases, also because they induce EMT as well as metalloproteinase (MMP)2 and MMP9 proteolytic activity in PDAC cells [87,88]. As recently demonstrated, the adverse effects of M2 TAMs on PDAC prognosis also depend on their ability to induce in cancer cells the expression of cytidine deaminase involved in the metabolism of gemcitabine thus preventing apoptosis during gemcitabine treatment [89]. Informations on the molecular pathways underlying M2 polarization in PDAC are scarse.…”
Section: Immunosuppressive Cellsmentioning
confidence: 99%
“…96 In vitro, macrophage-induced CDA upregulation in human Panc-1 pancreatic tumor cell line has been shown to confer gemcitabine resistance. 111 Data from ample studies have indicated that CDA polymorphisms alter CDA enzyme activity and the pharmacokinetics of gemcitabine, [135][136][137][138] and three functional polymorphisms of CDA (rs2072671, CDA 79A  C; rs60369023, CDA 208G  A; and rs1048977, CDA 435C  T) could predict the clinical outcomes of gemcitabine-based tumor chemotherapy. 33,135,136 …”
Section: Cdamentioning
confidence: 99%